Decentralizing Education in Guatemala : School Management by Local Communities - Rojas, Carlos; Valerio, Alexandria; Demas, Angela (World Bank, Washington, DC, 2012)
Guatemala set out in 1992 to increase access to education in remote areas. Its National Community-managed Program for Educational Development (PRONADE) has evolved from a small, innovative pilot program in 19 rural communities, to a nationwide program reaching over 4,100 communities and 445,000 children. PRONADE is one of the most proactive managerial, administrative, and financial decentralization measures taken in Latin America. Isolated rural communities have been truly empowered to administer and manage the schools. Following are some remaining challenges to be resolved for PRONADE continued success : quality issues and students learning outcomes must be dealt more systematically; PRONADE teachers have not received consistent training in multi-grade and bilingual classroom practices; impact evaluation are needed to determine how PRONADE is affecting student achievement, repetition, and drop-out rates, as well as teacher effectiveness; finally, there have been frequent delays in payment of teacher salaries, as well as transfer of funds for school snacks, educational and teaching materials.